Peran Ekstrakurikuler dalam Membangun Keterampilan dan Karakter Siswa Kegiatan SMA Katolik Sint Gabriel Maumere - Bernadeta Delviana; Matheus Mitan; Rusli Hereng (Lembaga Pengembangan Kinerja Dosen, 2025)
The formation of student character through education is an essential process to elevate human dignity. This study aims to determine whether extracurricular activities can be an effective means to shape student character, prepare them to face various challenges in life, and become positive contributors in society. The findings in the form of Character and Personality Development Extracurricular activities can also help in the development of student character and personality. They learn about responsibility, integrity, perseverance, and respect for others. These are values ​​that will help them become better and more successful individuals, namely OSIS, Choir, Traditional dance, Sports clubs, Social activities, The role of extracurricular activities in students' skills and character based on the results of interviews and observations shows that extracurricular activities contribute significantly to student skills: Communication, Cooperation, Leadership, Student character: Discipline, Responsibility Character and Personality Development Extracurricular activities can also help in the development of student character and personality. They learn about responsibility, integrity, perseverance, respect for others. These are values ​​that will help them become better and more successful individuals in the future, and finally Character and Personality Development Extracurricular activities can also help in the development of student character and personality. They learn about responsibility, integrity, perseverance, and respect.